Maternal depression in rural Pakistan: the protective associations with cultural postpartum practices - Katherine LeMasters; Nafeesa Andrabi; Lauren Zalla; Ashley Hagaman; Esther O. Chung; John A. Gallis; Elizabeth L. Turner; Sonia Bhalotra; Siham Sikander; Joanna Maselko (BMC, 2020)
Abstract Background Traditional postpartum practices are intended to provide care to mothers, but there is mixed evidence concerning their impact on postpartum depression (PPD). It remains unknown if there is a unique impact of postpartum practices on PPD separately from other types of social support, or if practices differentially affect those with existing prenatal depression. In Pakistan, chilla (چله) is a traditional postpartum practice in which women receive relief from household work, additional familial support, and supplemental food for up to 40 days postpartum. This study aims to understand if chilla protects against PPD independent of other support and whether this relationship varies by prenatal depression status. Methods Data come from the Bachpan cohort study in rural Pakistan. Chilla participation and social support (Multidimensional Scale of Perceived Social Support) were assessed at 3 months postpartum. Women were assessed for major depressive episodes (MDE) with the Structured Clinical Interview, DSM-IV and for depression symptom severity with the Patient Health Questionnaire (PHQ-9) in their third trimester and at 6 months postpartum. Adjusted linear mixed models were used to assess the relationship between chilla participation and PPD. Results Eighty-nine percent of women (N = 786) participated in chilla and almost 70% of those that participated took part in all of chilla's aspects. In adjusted models, chilla participation was inversely related to MDE (OR = 0.56;95%CI = 0.31,1.03) and symptom severity (Mean Difference (MD) = − 1.54;95%CI: − 2.94,-0.14). Chilla participation was associated with lower odds of MDE (OR = 0.44;95%CI = 0.20,0.97) among those not prenatally depressed and with lower symptom severity among those prenatally depressed (MD = -2.05;95%CI:-3.81,-0.49). Conclusions Chilla is inversely associated with both MDE and symptom severity at 6 months postpartum above and beyond social support. Specifically, chilla is inversely associated with MDE among those not prenatally depressed and with lower symptom severity among those prenatally depressed. This relationship signals an opportunity for interventions aimed at preventing and treating PPD in this region to draw upon chilla and similar traditional postpartum practices in creating community-based, low-cost, sustainable interventions for maternal mental health. Trial registration NCT02111915. Registered 18 September 2015. NCT02658994. Registered 22 January 2016. Both trials were prospectively registered.